Job Insecurity Selama Pandemi Covid-19 - Saragih, Susanti; Kodarisman, Renata Yeldiana (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Business uncertainty during the Covid-19 pandemic triggers feelings of threat and discomfort for employees in carrying out their work. Employees are afraid of losing their jobs and making work stress higher. This study aims to determine the effect of job insecurity, performance, work stress, and turnover intention on employees during the Covid-19 pandemic. There were 101 respondents from the service industry who participated in this study. The results of the study show that even though job insecurity is high during the pandemic, it does not make employees intend to move if they feel they are performing well. However, turnover intention will be higher if employees feel that the discomfort at work has made them stressed at work. This study provides several suggestions of important implications for organizations in managing human resources during the Covid-19 pandemic.